Confucius : great teacher of China - Demi (Shen's Books, 2018)
Provides an illustrated biography of Confucius describing his birth, education, and desire to become a teacher in order to transform people's thinking and change the world. Discusses how he believed rulers should be wise, trustworthy, and generous, and lead by example. Illustrates how Confucius' ideas about education, government, human behavior, and compassion continue to inspire others centuries later.